Securing Credible Elections in Africa Through ICT: An Appraisal of Nigeria: Array - Abdulkadir, Ameen A. I. (Acta Universitatis Danubius. Relationes Internationales, 2021)
This work examined the impact of Information and Communication Technologies (ICTs) in the conduct of credible elections in Africa with particular reference to Nigeria, which is no doubt, the largest democracy on the African continent. Many African countries have been challenged with the inability to conduct free, fair and credible election, hence the introduction of ICTs to serve as pathway to credible elections. The objectives of the study include; appraise the extent to which ICTs enhance credible electoral process in Nigeria; identify the strengths and possible weaknesses of the devices in the conduct of election. The study engaged interpretative case study for its research methodology. The interpretative method relies on analogical deductions and re-analysis of literature from secondary sources to generate new findings. Findings from this work show that, before the deployment of ICTs especially the sophisticated ones to secure electoral process, election has always been a monument of fraud and festival of violence. However, with the introduction of these technological innovations, it has been revealed that more strengths are inherent than weaknesses. It is therefore recommended that improved infrastructure particularly energy should be given priority to facilitate effective use of the equipment, because most polling stations particularly those in the rural areas complained of lack of electricity to power the gadgets. Also, electoral bodies should always have alternative (Plan B) in case an initial approach or facility fails. This is in addition to test-running all equipment before the election proper to make the election result credible and acceptable to the citizens.